Development of Bilimbi (Averrhoa bilimbi L.) Powder: Physicochemical, Microbial and Organoleptic Qualities - Nilugin, S.E.; Mahendran, T. (University of Jaffna, 2016)
Underutilized plant species are defined by their unexploited economic potential, making them an appropriate focus for commercialization. Fruits of these plants are an important supplement to human diet as they provide the essential minerals, vitamins and fibre required for maintaining health. A research was conducted to develop bilimbi fruit powder with good nutritional qualities and to assess the shelf life. Unripe mature bilimbi fruits were collected, washed and cut into 12 mm thick slices. The slices were dipped into potassium metabisulphite solution of 0.05 % (w/v) for 5 minutes. These slices were placed in a single layer on trays, dried in sun for 18 hours and in dehumidifier at 40 °C, 50 °C, 60 °C and 70 °C for 16, 14, 12 and 10 hours, respectively and ground into powder. The developed powders were assessed for physico-chemical, microbiological, sensory qualities and shelf life. Physico-chemical analyses revealed that among the tested treatments the powder developed from the unripe bilimbi dried at 50 °C had 3.4 % of moisture content, 1.4 % of fibre, 10.9 % of tritratable acidity (as % oxalic acid), 20.8 mg/100 g of ascorbic acid and 11.3 % of total sugar content. Microbiological analysis indicated that there was no total plate count observed in the tested treatments. Sensory attributes showed that powder developed from the unripe. bilimbi dried at 50 °C was most preferred based on the organoleptic characteristics. Among the treatments, the bilimbi powder obtained from the unripe bilimbi dried at 50 °C for 14 hours had the highest shelf life which could be preserved minimum of six months without any significant changes in the quality characteristics.
Keywords: Bilimbi powder; dehydration; organoleptic quality; physico-chemical characteristics